Evidence-based medicine: what it can and cannot do - Goffredo Freddi; José Luis Romàn-Pumar (Istituto Superiore di Sanità, 2011)
Evidence-based medicine (EBM) is not a old hat, a "cookbook" medicine perpetrated by arrogant to serve cost cutters to suppress clinical freedom, a mandatory, deterministic, totalitarian practice of medicine, a way to control cost and to ignore patient preferences, a limit to personal/humanistic/individual medicine. EBM is a reference of excellence to guide clinical decisions, the integration of own expertise with others' expertise and patient preferences, a way to improve medical practice and limit the variability and errors created when there is not evidence to identify the gold standard and differentiate among alternatives available. But evidences need to be integrated with a new thinking based on Complexity Science. Health care systems operates as complex adaptative systems rather than rigid, linear or mechanical organizations and innovation is a critical outcome of Complexity Science. How does EBM impact drug innovation? New drug approvals are not keeping pace with rising Research and Development spending, clinical approval success rate for new chemical entities (NCEs) is progressively dropping and maybe, through these indicators, we are seeing the worst face of EBM: its limiting, blocking, and controlling side. If that is the case, EBM is the main ally to keep the economy of health systems under control and the great excuse to block the access of the innovation to patients. Certainly not the best way to maximize the benefits of EBM.